Monitoring of physical and functional state of elite basketball players in covid-19 pandemic - Andrianova, R. I.; Fedoseev, D. V.; Lenshina, M. V.; Lubyshev, E. A. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to experimentally substantiate the method of control of the physical and functional state of highly-qualified basketball players amidst the COVID-19 pandemic.